2008
DOI: 10.1007/s11801-008-8067-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electrical properties of co-evaporated In, Garich CIGS thin films

Abstract: The CIGS thin films are prepared by co-evaporation of elemental In, Ga and Se on the substrates of Mo-coated glasses at 400°C followed by co-evaporation of elemental Cu and Se at 550°C. We study the structural and electrical properties using XRD, XRF and Hall effect measurements. In general, Cu(In,Ga) 5 Se 8 phase exists when Cu/(In+Ga) ratio is from 0.17 to 0.27, Cu(In,Ga) 3 Se 5 phase exists for Cu/(In+Ga) ratio between 0.27 and 0.41, Cu 2 (In,Ga) 4 Se 7 and Cu(In,Ga) 2 Se 3.5 phases exist for Cu/(In+Ga) rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…We suggested that the difficulty of n ‐type conductivity by Cd doping into CDL on CIGS surface to enhance conversion efficiency in CIGS solar cells owing to insufficient activation of Cd atoms. In Cu depletion condition, the carrier concentration is low owing to Cu vacancies, which represent acceptors, and antisite defect of In atoms onto Cu sites, which represent donors . Additionally, Cd can easily diffuse into CIGS in the case of Cu depletion during chemical bath deposition of the CdS layer, and Cd atoms located into Cu sites represent donors .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggested that the difficulty of n ‐type conductivity by Cd doping into CDL on CIGS surface to enhance conversion efficiency in CIGS solar cells owing to insufficient activation of Cd atoms. In Cu depletion condition, the carrier concentration is low owing to Cu vacancies, which represent acceptors, and antisite defect of In atoms onto Cu sites, which represent donors . Additionally, Cd can easily diffuse into CIGS in the case of Cu depletion during chemical bath deposition of the CdS layer, and Cd atoms located into Cu sites represent donors .…”
Section: Resultsmentioning
confidence: 99%
“…Each numbered point from 1 to 20 indicates the position analyzed by TEM-EDX (points 1, 5, 6, and 13 are not shown in these STEM images). B, Cu/(Ga + In) ratio determined by EDX measurements of the interior (points 1-4), surface (points 5-12), and boundaries (points 13-20) of CIGS grains of the sample with a Se irradiation time of 5 min [Colour figure can be viewed at wileyonlinelibrary.com]condition, the carrier concentration is low owing to Cu vacancies, which represent acceptors, and antisite defect of In atoms onto Cu sites, which represent donors 34,35. Additionally, Cd can easily diffuse into CIGS in the case of Cu depletion during chemical bath deposition of the CdS layer, and Cd atoms located into Cu sites represent donors 13,14.…”
mentioning
confidence: 99%
“…CIGS had resistivity and carrier concentration of 90 Ωcm and 2.0 × 10 17 cm −3 , while Cu(In,Ga) 3 Se 5 had that of 7.6 MΩcm and 6.1 × 10 13 cm −3 . It has been reported that carrier concentration decreases when CGI value decreases in Cu─In─Ga─Se system because antisite defect In Cu , which acts as donor, is formed . The spreading resistance R can be expressed according to Equation , where a and ρ are prove diameter and resistivity, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Our modeling indicated that measurement errors with NCLST and LLST techniques may occur due to front-contact sheet resistances if the absorber layer area conductivity is higher than 10 S/m 2 . Moreover, CIGS is a complex multi-component compound, and specific electric resistivity values could differ 10 5 times depending on the Cu/(In + Ga) ratio (Kwon et al, 1998;Xue et al, 2008). Therefore, the top-contact serial resistance effect has to be considered very carefully when interpreting the electrical measurement.…”
Section: Discussionmentioning
confidence: 99%